Implementation of an Integrated Quality Assurance System in Improving Learning Quality - Lestari, Renda; Idrus, Ali; Hadiyanto, Hadiyanto; Sulistiyo, Urip (PPSDP International Journal of Education, 2023)
The purpose of this research is to find out how the system, principles of improvement, and model of developing an integrated quality assurance system improve the quality of learning. Judging from the type, this research is library research including the type of library research. Library research is research, whose data collection is done by collecting data from various literatures. The approach used in this research is a qualitative approach, which emphasizes its analysis of the process of drawing comparative conclusions and on analyzing the dynamics of the relationship between observed phenomena using scientific logic. The data were analyzed by data reduction, data display, and conclusion drawing. The results showed that there are management procedures and tools for creating qualitative changes in learning quality. Starting from the input in the form of policies, systemized application processes, and outputs in the form of achieving the profile and quality of graduates.